Pengaruh Metode Bernyanyi Terhadap Peningkatan Hasil Belajar Siswa pada Mata Pembelajaran IPS Kelas III - Sari, Ayu Nopita; Heldayani, Eni; Prasrihamni, Mega (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
Social Sciences (IPS) is a very important science to learn, especially for elementary school children.Social studies education is directed at the process of developing the potential of students to be sensitive to social problems that occur in society, as well as a sense of responsibility as members of society and the nation. The purpose of this study was to determine student learning outcomes in social studies learning class III SDN 222 Palembang. The method used is quantitative research with purposive sampling technique that is based on certain considerations. For data collection techniques, tests, observations and documentation were carried out. The influence technique in this study was carried outthrough hypothesis testing with t-test. Based on the calculation of learning outcomes, the average value for the initial test was 61.79 and the final test increased to 78.93, and through the t-test the value of tcount = 3.779 was greater than the value of ttable = 2.005, this indicates that the hypothesis is accepted, namely there is a significant effect of the singing method on social studies learning outcomes for third grade students at SDN 222 Palembang.